1999
DOI: 10.1136/gut.44.3.400
|View full text |Cite
|
Sign up to set email alerts
|

The role of psychological and biological factors in postinfective gut dysfunction

Abstract: Background-Both psychological and physiological disturbances have been implicated in the aetiopathogenesis of irritable bowel syndrome (IBS). Aims-To investigate how the psychological factors act, and the involvement of infective and physiological factors. Methods-Consecutive patients hospitalised for gastroenteritis reported life events for the previous 12 months, and past illness experiences on standardised questionnaires. They also completed psychometric questionnaires for anxiety, neuroticism, somatisation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
398
2
10

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 676 publications
(425 citation statements)
references
References 41 publications
13
398
2
10
Order By: Relevance
“…Overall, these findings support the hypothesis that severity of exposure and/or prolonged exposure increases risk of IBS. Previous studies have hypothesized that psychological stress may increase or sustain inflammatory response to infection and increase the risk of IBS [22,26,28,32,[35][36][37]. To evaluate this, we used a prior history of consultation (within 1 year) for psychological and social problems as a proxy indicator for presence of psychological stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, these findings support the hypothesis that severity of exposure and/or prolonged exposure increases risk of IBS. Previous studies have hypothesized that psychological stress may increase or sustain inflammatory response to infection and increase the risk of IBS [22,26,28,32,[35][36][37]. To evaluate this, we used a prior history of consultation (within 1 year) for psychological and social problems as a proxy indicator for presence of psychological stress.…”
Section: Discussionmentioning
confidence: 99%
“…Severity of GE (duration of diarrhoea, presence of blood in stools, abdominal cramps, weight loss), younger age and female gender have been associated with increased risk of PI-IBS [21,[28][29][30][31][32][33][34]. Anxiety, depression and major life events have also been identified as potential risk factors with some hypothesizing that these disorders prolong gut inflammation and heighten sensory perception [22,26,28,29,32,[35][36][37]. Several studies have found increased healthcare-seeking behaviors in IBS patients but reasons for this are not well understood [15,16,33,38].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the role of microscopic inflammation and immune activation in the intestinal mucosa has been elucidated. 3,5,22 Gastrointestinal infections are more likely to initiate IBS-like symptoms 23 inducing mucosal inflammation. Impaired intestinal permeability 24 and a role for mucosal inflammation in regulating the gut-brain axis 25 have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in gastrointestinal motor function, enhanced visceral perception of painful stimuli and psychosocial factors are considered as key contributors to symptom generation in IBS (2,23) . Factors that are receiving recent attention include reduced ability to expel intestinal gas, altered central processing of afferent signals and intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%